2016
DOI: 10.1007/s13224-016-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Polyps and Subfertility

Abstract: Endometrial polyps are frequently seen in subfertile women, and there is some evidence suggesting a detrimental effect on fertility. How polyps contribute to subfertility and pregnancy loss is uncertain and possible mechanisms are poorly understood. It may be related to mechanical interference with sperm transport, embryo implantation or through intrauterine inflammation or altered production of endometrial receptivity factors. Different diagnostic modalities such as two-or three-dimensional transvaginal ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 32 publications
(35 reference statements)
4
48
0
6
Order By: Relevance
“… 10 - 13 Uterine masses like polyps and fibroids are known to affect the implantation in various ways, including increased uterine contractions, abnormal vascularization, and, especially, chronic inflammation. 14 - 16 In our study we found over 50% of the patients had polyps and fibroids after surgical removal.…”
Section: Discussionsupporting
confidence: 45%
“… 10 - 13 Uterine masses like polyps and fibroids are known to affect the implantation in various ways, including increased uterine contractions, abnormal vascularization, and, especially, chronic inflammation. 14 - 16 In our study we found over 50% of the patients had polyps and fibroids after surgical removal.…”
Section: Discussionsupporting
confidence: 45%
“…The presence of polyp may hinder implantation and cause infertility. 13 In a study including 224 female infertility patients, pregnancy rates improved by 50% after polypectomy. 14 All cases of endometrial polyps found in our study underwent polypectomy.…”
Section: Resultsmentioning
confidence: 99%
“…It is usually asymptomatic and identified during the routine workup of AUB and/or infertility. [ 7 ] If the sutures used during CS undergo inappropriate hydrolysis and absorption, the retained intrauterine sutures may cause intrauterine inflammations with subsequent AUB and/or infertility. [ 2 3 ]…”
Section: Discussionmentioning
confidence: 99%
“…This case report highlights that the retained intrauterine sutures may interfere with sperm transport and implantation and act as FB with subsequent intrauterine inflammation and infertility. [ 7 ] In addition, the presented case highlights the role of the hysteroscopy as the gold standard procedure for uterine cavity assessment in women presented with AUB and/or infertility. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%